2018
DOI: 10.3390/plants7020026
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Silicon Amendment for Improved Wheat Production

Abstract: Many studies throughout the world have shown positive responses of various crops to silicon (Si) application in terms of plant health, nutrient uptake, yield, and quality. Although not considered an essential element for plant growth, Si has been recently recognized as a “beneficial substance” or “quasi-essential” due to its important role in plant nutrition, especially notable under stressed conditions. The goal of this study was to evaluate the effect of Si on wheat plant height, grain yield (GY), and grain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 38 publications
0
8
0
2
Order By: Relevance
“…Most of the absorbed Si was accumulated in the shoot tissue, where it is deposited within the leaf epidermis through plant transpiration flux. The Si inside plant epidermis was condensed into a polymerized silica gel (SiO 2 nH 2 O) known as a phytolith that is immobile and developed a protective structural layer in the plant cell walls [ 36 , 37 , 38 ]. Interestingly, we verified that grain Si accumulation in maize and wheat also increased with silicate application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the absorbed Si was accumulated in the shoot tissue, where it is deposited within the leaf epidermis through plant transpiration flux. The Si inside plant epidermis was condensed into a polymerized silica gel (SiO 2 nH 2 O) known as a phytolith that is immobile and developed a protective structural layer in the plant cell walls [ 36 , 37 , 38 ]. Interestingly, we verified that grain Si accumulation in maize and wheat also increased with silicate application.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies reported that sugarcane ( Saccharum officinarum L.) has the potential to take up the largest amount of silicon (300–700 kg of Si ha −1 ), followed by rice (150–300 kg of Si ha −1 ), and wheat (30–150 kg of Si ha −1 ) [ 41 ]. On an average, plants can absorb anywhere from 30 to 300 kg Si ha −1 [ 38 , 42 ]. Such values of absorbed silicon cannot be fully explained by passive absorption because the upper 0.20 m soil layer contains only an average of 0.1–1.6 kg Si ha −1 as monosilicic acid [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study in which the effect of silicon was examined on wheat production was conducted in Idaho [ 17 ]. Three concentrations of Si, i.e., 140, 280, and 560 kg Si∙ha −1 for fertilization, were applied in the form of amorphous volcanic tuff.…”
Section: Cerealsmentioning
confidence: 99%
“…In New Jersey, in a three consecutive years of field experiment, calcium silicate (steel slag by-product) was added on a Quakertown Silt Loam soil increasing yield up to 10%, but only under biotic stress imposed by powdery mildew [57]. A two consecutive growing seasons experiment performed in Idaho evaluated the application of Si in the form of amorphous volcanic tuff in the Greenleaf-Owyhee Silt Loam soil indicated that there was no significant effect of Si on plant height, nutrient uptake, grain yield and grain protein content of winter wheat grown in non-stressed conditions [58]. A three site-years experiment was conducted on the Alluvial Floodplain soils in Louisiana to evaluated silicate slag applications on productivity of wheat under sufficient and high nitrogen application rates showed a numerical trends of grain yield increase increasing silicate slag rate, but significant increase was only observed in one site and year [59].…”
Section: Silicon and Wheat Yieldmentioning
confidence: 99%